Penerapan Asuransi dalam Pembiayaan Kredit Pemilihan Rumah (KPR) FLPP pada PT Bank Sumut Syariah Kantor Cabang Pembantu Perdagangan - Devia Astry Khairani; Aqwa Naser Daulay (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
This article discusses the application of insurance in Financing Credit for Affordable Housing Ownership (KPR FLPP) by PT. Bank Sumut Syariah Branch Office of Trade Auxiliary. The objectives of this study are to identify the role of insurance in mitigating credit risks in FLPP KPR financing and to evaluate its effectiveness in the context of Islamic banking services. The method employed involves primary data collection through interviews with bank officials and insurance policyholders, as well as secondary data analysis of historical insurance claim data and credit performance. The research findings indicate that the application of insurance in FLPP KPR financing can enhance the bank's confidence in credit risk management, provide financial protection for the bank, and ensure smooth installment payments for customers. In conclusion, insurance in FLPP KPR financing plays a strategic role in supporting the sustainability of Islamic banking business by effectively managing credit risks.